The traditional game of TAPA GALA as a method to improve gross motor skills - Haq, Idharul; Satriawan, Rabwan; Irawan, Ewan (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Gross motor skills are essential for supporting the physical development of primary school-aged children; however, the increasing use of digital devices reduces their engagement in traditional physical activities. The purpose of this study is to test the effectiveness of the traditional Tapa Gala game in improving the gross motor skills of fourth-grade students at SDN 2 Tawali Wera. This study uses a quasi-experimental method with a one-group pre-test and post-test design, involving 12 students aged 9–10 years. The Tapa Gala Gross Motor Test (TMK-TG) includes four subtests: Zig-Zag Running, Standing Long Jump, Chasing Running, and Imitating Movement. The data were analyzed using paired t-tests to determine significant differences between the pre-test and post-test scores. The results showed a significant improvement in gross motor skills following the intervention, with an average pre-test score of 40.25 and a post-test score of 50.42 (p = 0.000; p < 0.05). Based on the classification, 25% of students were in the “Very Good” category, 67% in the “Good” category, and 8% in the “Sufficient” category. These results indicate that the traditional Tapa Gala game can be effectively implemented as a contextualized, enjoyable, and culturally rich physical learning method to support children’s gross motor development. This study provides further evidence that games based on local wisdom can serve as an alternative learning strategy to support students’ physical competence while preserving traditional games within modern education. Keywords: gross motor; traditional games; Tapa Gala